Design of a mango leather maker for rural people - Masum, Habib; Tarafdar, Bikarna; Molla, M Jahir Anwar; Mondal, Ishani (Journal of Postharvest Technology, 2023)
Mango leather is a very popular and lovable product of mango with sweet and sour in Teste. The leather can be prepared in the open-air sun drying traditional process or using different drying machines like microwave ovens, deep freezers, and industrial machines for commercial purposes. The preparation of mango leather in rural areas is mostly confined to the traditional open-air sun-drying process. The open-air drying process is unhygienic, lengthy, weather dependent, and requires continuous monitoring. This research work proposes a new mango leather maker to facilitate a semiautomatic mango pulp drying process by addressing the issues of the open-air sun-drying process. The proposed system is an IoT-based device that implements advanced controlled drying in addition to the sun-drying process. The leather preparation will be done within the closed chamber to maintain the desired hygiene. It’s a weather-independent, low-cost, simple operation, and speedy drying process which can be operated by any individual with very little attention. The initial investment as well as operating cost of the maker is very low, hence, it can create a new business opportunity and improve the livelihood of rural people, particularly, rural house makers.